2020
DOI: 10.1365/s42681-020-00015-0
|View full text |Cite
|
Sign up to set email alerts
|

Grandiose narcissism and performance in organizations: mediating role of subjective wellbeing

Abstract: Narcissism is imbued with emotional dynamism and there is a strong need to assess the linkages with outcomes by analyzing their fusion. The present study examined the relationship between grandiose narcissism and performance through analyzing the mediating role of subjective wellbeing (positive affect, negative affect and life satisfaction). The wholesome assessment of performance was done by considering task performance, team-work and cognitive motivational effectiveness among 293 senior-level Indian employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…It was found that happiness level was positively correlated with narcissism level. Although some studies in the literature suggest otherwise [48,52], most studies support the findings [41][42][43][44][45][46][47][48][49]. Because of the inconsistency of the scales of narcissism, it was normal to have opposite results in this way [71].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that happiness level was positively correlated with narcissism level. Although some studies in the literature suggest otherwise [48,52], most studies support the findings [41][42][43][44][45][46][47][48][49]. Because of the inconsistency of the scales of narcissism, it was normal to have opposite results in this way [71].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was seen that some studies found positive associations between healthy narcissism and happiness [41][42][43][44][45][46][47][48][49], and some found a negative relationship between unhealthy narcissism and happiness [41,43,44,50,51]. However, some studies found a positive relationship between unhealthy narcissism and happiness [48,52]. Many studies found a positive relationship between gaming disorder and narcissism [53].…”
Section: Gaming Disorder Narcissism and Happiness And The Present Researchmentioning
confidence: 99%
“…Narcissistic leadership has been described as a personality disorder in which there is a strong need for power and self-love, derived from its description of the destructive organizational behaviors of senior executives and politicians, with its focus on the psychological components of arrogance, arrogance, and low levels of empathy (Sudha & Shahnawaz, 2020). Narcissistic leadership has occupied a degree of interest in the literature in general for its negative impact on workers' performance because they tend to be more willing to take revenge, less willing to forgive, more angry and impulsive, and more aggressive (Bilevicius et al, 2019).…”
Section: Introductionmentioning
confidence: 99%